(untitled) (XXI Century. Spanish Literature and Culture, 2008)
Volver al mundo constitutes an exceptional case in the Spanish reception of Friedrich Hölderlin. Assuming the slope of the literary modernity inaugurated by the German author more than two centuries ago, the novel of González Sainz discovers the implications that its message acquires transferred to a context of political disenchantment. Its great contribution to contemporary Spanish narrative consists in undertaking this problematic from its linguistic root: on the one hand, González Sainz discovers the manipulation that conceals all ideological appropriation of language, on the other hand, explores the possibilities that offers the novelistic genre to plant a critical discourse in front of this reality. The present article examines the different forms of meeting and separation that Volver al mundo tests with the work of Hölderlin, to discover how all of these open to a reevaluation of literary language and its capacity for investigation.